2013
DOI: 10.1371/journal.pone.0055562
|View full text |Cite
|
Sign up to set email alerts
|

Rising CO2 Interacts with Growth Light and Growth Rate to Alter Photosystem II Photoinactivation of the Coastal Diatom Thalassiosira pseudonana

Abstract: We studied the interactive effects of pCO2 and growth light on the coastal marine diatom Thalassiosira pseudonana CCMP 1335 growing under ambient and expected end-of-the-century pCO2 (750 ppmv), and a range of growth light from 30 to 380 µmol photons·m−2·s−1. Elevated pCO2 significantly stimulated the growth of T. pseudonana under sub-saturating growth light, but not under saturating to super-saturating growth light. Under ambient pCO2 susceptibility to photoinactivation of photosystem II (σi) increased with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
96
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(108 citation statements)
references
References 78 publications
(113 reference statements)
10
96
2
Order By: Relevance
“…Furthermore, maximum growth rates were comparable to previously reported values for this strain; ∼0.9 d −1 at 18 • C and 80 µmol photons m −2 sec −1 (Li and Campbell, 2013). In contrast to other studies, we found that the thermal optimum range (17.0 and 20.1 • C, centered on 18.6 • C) was slightly colder than previously reported values (Thompson et al, 1992;Boyd et al, 2015) and may be due to the lower growth irradiance used in our study (Sandnes et al, 2005).…”
Section: Temperature Driven Changes In Fitness and Other Functional Tsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, maximum growth rates were comparable to previously reported values for this strain; ∼0.9 d −1 at 18 • C and 80 µmol photons m −2 sec −1 (Li and Campbell, 2013). In contrast to other studies, we found that the thermal optimum range (17.0 and 20.1 • C, centered on 18.6 • C) was slightly colder than previously reported values (Thompson et al, 1992;Boyd et al, 2015) and may be due to the lower growth irradiance used in our study (Sandnes et al, 2005).…”
Section: Temperature Driven Changes In Fitness and Other Functional Tsupporting
confidence: 89%
“…In contrast to other studies, we found that the thermal optimum range (17.0 and 20.1 • C, centered on 18.6 • C) was slightly colder than previously reported values (Thompson et al, 1992;Boyd et al, 2015) and may be due to the lower growth irradiance used in our study (Sandnes et al, 2005). In terms of morphological traits, absolute cell volumes were within range of previously reported values (Li and Campbell, 2013) and consistent with Thompson et al (1992), with cells becoming larger with increasing temperature (Figure 3A). These changes in cell volume, although small (i.e., ∼10%), may have significant implications for vertical export of carbon, as has been demonstrated in other small, spherical phytoplankton taxa (coccolithophores; Pantorno et al, 2013).…”
Section: Temperature Driven Changes In Fitness and Other Functional Tsupporting
confidence: 55%
“…The PAR intensity that initiated the NPQ of N-limited grown cells was one fourth of that of N-replete grown ones. Light history would affect the photophysiological performances of phytoplankton when being shifted from the indoor-to outdoor-conditions, such as the S. costatum strain maintained in the laboratory for decades showed differential responses to UV compared to the strain isolated from coastal water (Guan and Gao 2008), and the Thalassiosira pseudonana showed differential photoinactivations of photosystem II after acclimating to different light levels (Li and Campbell 2013). In natural environments, the light acclimation from very low to very high levels with or without UVR also happens, such as that after typhoon event (Li et al 2009) or after heavy cloud covers for days or during a diel cycle (Gao et al 2007a), which would cause the exaggerated photoinhibition of S. costatum by solar PAR or UVR (Figs 2 & 3) although this diatom species could rapidly acclimate to the field light conditions (Guan and Gao 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with recommendations in best practice guides [38], we used a continuous culture system with CO 2 -enriched gas aeration to achieve stable carbonate chemistry that mimics the natural changes occurring due to ocean acidification. For a better understanding of how individual species will respond under natural conditions, we conducted our experiments at macronutrient concentrations reported for the area from which our strains were isolated (near shore coastal waters off Davis Station, Antarctica) and set the light intensity to a similarly high level, as light intensity can greatly alter the CO 2 -induced response of phytoplankton [39][40][41]. Furthermore, we chose to expose all species to continuous light to minimize diurnal variations which can mask CO 2 -induced changes [42].…”
Section: Methodsmentioning
confidence: 99%